Options for Better Quality and More Accessible Long-term Care Services for the Elderly in Poland : Policy Note - Kerschbaumer, Florentin (World Bank, Washington, DC, 2020)
This note is prepared as a continuation of the long-standing collaboration between the Government of Poland and the World Bank in the area of Long-Term Care (LTC). Some of the earlier outputs of this collaboration include the 2009 report Long-Term Care and Ageing which examined the fiscal challenges arising from a growing need for LTC in the context of an aging society, and the 2015 report the Present and Future of Long-Term Care in Ageing Poland, which outlined the key challenges and opportunities for developing a delivery and financing system for LTC for the elderly. More recently, the 2017 World Bank Technical Assistance (TA) culminated in the international conference Long Term Care Systems Design and Financing which focused the attention of policymakers and the international community on options for an integrated LTC system as well as demonstrating the fiscal and economic implications of adopting various LTC modalities. Importantly, the conference showcased the capacity of the World Bank to convene a broad range of stakeholders and to bring the latest know how to support this agenda. The LTC agenda is receiving much attention in Poland’s public debate. Rapid population ageing, a result of increasing longevity and declining fertility, generated significant demographic challenges and it is now clear that these necessitate adjustments to the current LTC system. Eurostat forecasts that the old-age dependency ratio will increase from 14 to 28 percent of the population by 2060. The older the population will become, the more people will face difficulties with regards to their activities of daily living and the higher will be the incidence of dependency in the overall population. This, in turn, spurs increases in the demand for various forms of care, both medical and social. Some of this demand is met by families through provision of familial care. However, informal care provision negatively affects earning and incomes of families and contributes to the overall labor shortage in the country. Continuous reforms are therefore needed, both in the health and social sectors, as well as in the labor market to meet these emerging needs.